Modern understanding of latent autoimmune diabetes in adults - I. I. Golodnikov; N. V. Rusyaeva; T. V. Nikonova; I. V. Kononenko; M. V. Shestakova (Сахарный диабет)
Latent autoimmune diabetes in adults (LADA) according to various sources is from 4 to 12% of all cases of type 2 diabetes mellitus (T2DM). Its uniqueness lies in the simultaneous combination of autoantibodies to β-cells (characteristic of T1DM) and the possibility of treatment with oral hypoglycemic drugs (characteristic of T2DM) for at least 6 months. This is based on the pathogenesis common for T1DM and T2DM — the presence of an autoimmune reaction with the simultaneous involvement of adaptive and innate immunity, as well as, to a lesser extent, insulin resistance and a number of components of the metabolic syndrome. LADA has more in common with T1DM — the same stages in the development of the disease, from genetic predisposition to the undoubted development of insulin dependence, the difference lies in the duration of each of the periods and the age of manifestation. LADA is characterized by an older age of manifestation of 30–35 years and a slower rate of destruction of β-cells. This article presents data on the diagnosis, progress of LADA, its similarities and differences with other types of DM, and immunological features. The article also analyzes the modern approach to the treatment of patients with LADA and promising methods of treatment. The search for information was processing in published sources attached to the search engines PubMed, Google Scholar, Scopus, Web of Science, eLibrary.ru over the past 10 years. The following medical subject headings were used: latent autoimmune diabetes in adults, diabetes mellitus type 1 and 2, immunology, pancreas, genetic, treatment in various combinations using OR and AND logical operators.